Alcohol use disorder relapse factors: an exploratory investigation of craving, alcohol dependence severity, and meaning in life. (3rd September 2022) - Sliedrecht, Wilco; Seesink, Henk Jan; Vrijmoeth, Cis; de Waart, Ranne; Wiers, Reinout W.; Ostafin, Brian; Schaap-Jonker, Hanneke; Roozen, Hendrik; Witkiewitz, Katie; Dom, Geert
Abstract: For decades predictors of alcohol use disorder (AUD) relapse have been studied, and around 40 different clinical and demographic relapse determinants have been identified. This paper aims to investigate the relationship of two of these AUD relapse factors, namely craving and meaning in life (MiL). We hypothesized that greater meaning in life would be associated with lower cravings and lower relapse rates. An AUD subsample of 81 patients within a clinical population that participated in ongoing exploratory research on religious/spiritual factors related to substance use disorders was followed up to 1 year. Craving (as measured with the Penn Alcohol Craving Scale) and meaning in life (as measured with the Meaning in Life Questionnaire- presence subscale) measures were assessed at baseline and relapse was assessed at 6- and 12-month follow up. Main effects and the interaction between craving and meaning in life in predicting alcohol relapse (with relapse defined as 'any alcohol use' and ≥ 3 consecutive days of drinking) were calculated/subject of analyses. We also investigated the relationship between relapse and alcohol dependence severity as measured with the Leeds Dependence Questionnaire. Baseline craving and dependence severity were related to relapse, but there were no associations between meaning in life and levels of craving or alcohol relapse. Our findings suggest a need for additional research on characterizing the Meaning in Life concept.